PENGARUH FAKTOR INTERNAL TERHADAP KEPUTUSAN PEMBELIAN BUKU PERKULIAHAN PADA MAHASISWA S1 STIE INDONESIA BANJARMASIN - Siti Munawaroh; Hj. Masithah Akbar (Universitas Lambung Mangkurat, 2015)
The book is an asset for a student to add insight and knowledge. A student can not just expect the material of his teachers, but also must independently seek lecture material to supplement and clarify the material received in class. One way is to buy a book of lectures. This study aimed to determine the effect of motivation and attitudes towards decisions to buy book of lectures on S1 students of STIE Indonesia Banjarmasin. This research is quantitative with descriptive analytic design. The population in this research is 246 students. The samples are 152 students were taken by accidental sampling. Instruments used in the form of a questionnaire. Univariate analysis of data in the form of a frequency distribution, and in multivariate linear regression. The results showed that students were motivated moderate (65.8%), high motivation (29.6%) low motivation (4.6%). To the fact that most have a positive attitude (97.4%), negative attitudes (2.6%). As for the decision to buy a book of lectures largely decided to buy a book of lectures (74.3%) and decided not to buy a book of lectures (25.7%). Simultaneous testing showed that Fcount = 19.278 > Ftable = 3.06. Partial test for motivation variables show that tcount = 1.790 < ttable = 1.976, for the attitude variable tcount = 4.684> ttable = 1.976. The conclusion of this research is that the motivation and attitude simultaneously influence on the decision to buy book of lectures. Partially, motivation does not affect on the decision to buy book of lectures, but attitudes influence on the decision to buy book of lectures